Pengaruh Audit Operasional dan Sistem Pengendalian Manajemen Terhadap Peningkatan Efektivitas Produksi Pabrik Kelapa Sawit Di PTP Nusantara V Kebun Tandun - Arvando, Rifa; Rodiah, Siti; Suci, Rama Gita (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study aims to examine how much influence operational audit and management control system have on increasing production effectiveness. This research is quantitative with the method of collecting data using a questionnaire (questionnaire), the data obtained is processed using SPSS version 25. The sample in this study was 40 employee respondents who worked at PTP Nusantara V Kebun Tandun. Multiple regression analysis was used to test the hypothesis. The results of this study indicate that partially operational audit has no and no significant effect on increasing production effectiveness and management control systems have a positive and significant effect on increasing production effectiveness.